Tera Gymnastic Effective for Patient with Hypertension - Hesti Platini; Sandra Pebrianti; Indra Maulana (Faculty of Nursing Universitas Padjadjaran, 2019)
Hypertension is a cardiovascular disease globally. Hypertension is remains silent killer, the clinical strategy to focusing on new and improved treatments is exercise. Tera gymnastics is a physical and mental exercise, combining the movement of body parts with breathing techniques and rhythms through the concentration of thought that is carried out regularly, harmoniously, correctly and continuously, Physical activity can reduce high blood pressure. Some study showed Regular physical activity is an effective intervention with respect to these factor, decreasing mortality rate for cardiovascular disease and all cause of disease in hypertensive patient. Gymnastic Tera exercise can help to control metabolic variable related to hypertension. The study was use quasy experimental design with one group pretest-posttest. The study was conducted in Puskesmas Pasundan Garut. Sampling in this study is subjects that is criteria patients has hipertension with 8 weeks treatment so will take methode of concecutive sampling with 15 respondents for intervention group and 15 for control group. The sample were age 30-55 years. The Intervention was gymnastic tera exercise. The Blood pressure function was evaluated before and after the training period. The data were analyzed by using t-test paired. The result showed a significant difference before and after tera gymnastic exercise in patient with hypertension I (p=000.0). Result of systolic blood presure when in mean SD pretest is 146.00 higher than post test is 136.00 in intervention group. The tera gymnastic exercise conditioning program achieved effect in this population. The reduction of blood pressure after exercise is of great clinical relevance. The increased riskof physical inactivity in controlling hypertension in our study suggest that general practitioners must be in the habit of prescribing practice of physical exercise. Physical activity has been shown to have beneficial effect on blood pressure. patients are followed up regularly to confirm that they are adhering to the management plan and the blood pressure targets.